The Influence of Spray Parameters on Heat Transfer Characteristics in Spray Cooling - Liu Ni; Li Lirong; Huang Qianwei; Zhong Zemin (Zhileng xuebao)
Testing system is built up to study the heat transfer characteristics of micro-structure and smooth surface under the conditions of different spray height and spray pressure. The experiment is carried out in a closed loop spray cooling system with water as the working fluid with high speed camera. The experimental results indicate that both the spray height and spray pressure play more significant role in the spray cooling performance of the micro-structure surface than smooth surface. When the spray height staying in a high level, decreasing it until the critical height as indicated can obviously improve the heat flux, acquire higher CHF; Continually reducing the spray height can still slightly improve the heat flux, but a large margin reduction of the spray height can result in a decrease of heat flux and even delay the time of transition to two phase region. Thus the influence of spray height has two sides, different from the spray pressure, whose effect is monistic. Increasing the spray pressure can improve the heat flux and enhance the uniformity of the temperature distribution, especially in single phase region, and the heat flux increase obviously until to a stable value with the increasing of spray pressure.